Scenario mechanisms for realization of priority directions of socio-economic development of cross-border regions (on the example of tourism development in Chernivtsi Region) - Кифяк, Олександр (Suceava :Editura Universitatii “Stefan cel Mare”, 2017)
The monograph covers theoretical, methodological and applied aspects of scenario forecasting of social and economic development of cross‐border regions. Scientific research contributed to the systematization and synthesis of theoretical provisions of scenario forecasting, determination of scenario approach methods and peculiarities of their use in the development strategies of cross‐border regions. Based on the comprehensive analysis of the socio‐economic development of cross‐border regions, the positioning of the regions of Ukraine according to the level of effectiveness of the use of development potential and the state of social development of cross‐border regions (on the materials of cross‐border regions of Carpathian region) was assessed. Attractive dominant of optimistic scenario of social and economic development of cross‐border regions is substantiated in this work, priority directions and scenario mechanisms of their implementation are proposed. Based on the example of trade enterprises of the region the Strategy for the Development of Competitiveness has been developed.
Keywords: Tourism, socio-economic development, cross-border regions